The attitude of female students from expatriate communities and female citizens towards social responsibility in Makkah Al-Mukarramah (The International Journal for Scientific Research, 2025)
The study aimed to identify the level of attitudes toward social responsibility among national and expatriate female secondary school students in Makkah City. The descriptive method was employed, and the Social Responsibility Scale developed by Al-Nabrawi et al. (2021) was applied. The scale consists of four dimensions: environmental responsibility, educational responsibility, social solidarity, and citizenship and belonging. The sample was randomly selected and included 332 female students from secondary schools in Makkah. The results revealed that the level of social responsibility among both expatriate and national female students was high overall and across all four dimensions (environmental responsibility, educational responsibility, social solidarity, and citizenship and belonging). Moreover, the findings indicated statistically significant differences in attitudes toward social responsibility and its four dimensions in favor of the expatriate students. The researchers recommended enhancing these attitudes through well-planned and purposeful lessons and topics to be integrated into the school curricula, as well as training teachers to foster and strengthen students’ attitudes toward social responsibility.
Keywords: Social Responsibility; Environmental Responsibility; Educational Responsibility; Social Solidarity; Citizenship and Belonging